Immunological alterations in patients with primary tumors in central nervous system - Peraçoli, Maria Terezinha S. [UNESP]; Montelli, Terezinha C. B.; Soares, Angela M. V. C.; Parise-Fortes, Maria R.; Alquati, Sislaine A. B.; Ueda, Anete; Montenegro, Mario R.; Alves, Armando; Gabarra, Roberto C.; Faleiros, Tadeu P.; Zanini, Marcos A. (FapUNIFESP (SciELO), 1999)
Natural killer (NK) cells play an important role in immune surveillance against tumors. The present work aimed to study the cytotoxic activity of NK cells and T cell subsets in peripheral blood of 13 patients with primary tumors in central nervous system (CNS). As controls 29 healthy subjects with the age range equivalent to the patients were studied. The methods employed were: a) determination of cytotoxic activity of NK cells towards K562 target cells, evaluated by single cell-assay; b) enumeration of CD3+ lymphocytes and their CD4+ and CD8+ subsets defined by monoclonal antibodies; c) the identification of tumors were done by histologic and immunochemistry studies. The results indicated that adults and children with tumor in CNS display reduced percentage of total T cells, helper/inducer subset and low helper/suppressor ratio. The cytotoxic activity of NK cells was decreased in patients with CNS tumors due mainly to a decrease in the proportion of target-binding lymphocytes. These results suggest that cytotoxic activity of NK cells may be affected by the immunoregulatory disturbances observed in patients with primary tumors in CNS.
Keywords: Brain tumors; NK cells; T cell subsets